2022
DOI: 10.1007/s00170-022-10673-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced abrasive-mixed-µ-EDM performance towards improved surface characteristics of biodegradable Mg AZ31B alloy

Abstract: The non-degradable metallic implants, such as bone screws, often act as the source of dysfunction and harmful corrosion products in the aqueous environment inside the human body. Many of these implants are fixed either temporarily or permanently into the human body, and therefore, both need to match tight tolerances with a remarkably finished surface to eradicate burrs or striations. In this regard, the new generation of degradable magnesium (Mg) alloy implants with excellent osseointegration and low elasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Therefore, a few studies have proposed the addition of conductive abrasive particles to EDM (AM-EDM) to substantially lessen the structuring of micro-cracks on the processed Mg alloys. For instance, as outlined by two recent experimental investigations, Zn-abrasive-assisted µ EDM minimized the surface micro-cracks and thus achieved remarkable surface modification in terms of superior corrosion resistance on Mg alloys over the unmachined specimen [ 18 , 30 ]. However, it can be argued that the studies on AM-EDM of Mg alloys suffered from certain weaknesses, such as excess thickness and inadequate uniformity of recast layer, which resulted in the poor surface quality of Mg alloys [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a few studies have proposed the addition of conductive abrasive particles to EDM (AM-EDM) to substantially lessen the structuring of micro-cracks on the processed Mg alloys. For instance, as outlined by two recent experimental investigations, Zn-abrasive-assisted µ EDM minimized the surface micro-cracks and thus achieved remarkable surface modification in terms of superior corrosion resistance on Mg alloys over the unmachined specimen [ 18 , 30 ]. However, it can be argued that the studies on AM-EDM of Mg alloys suffered from certain weaknesses, such as excess thickness and inadequate uniformity of recast layer, which resulted in the poor surface quality of Mg alloys [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Te analysis revealed that the cryogenic treatment would reduce electrode wear and improve MRR. Davis stated that [8] cryogenic treatment reduced adhering particles, micropores, and cracks on the surface of the sample. Davis and Singh stated that [9] powder or abrasive-mixed-microelectric discharge machining (A-M-EDM) is gaining popularity for performing precise machining and simultaneously modifying micromanufactured surface tables for clinical applications.…”
Section: Introductionmentioning
confidence: 99%